Instructor’s direct and indirect feedback: how do they impact learners’ written performance? - Lee, Luan Ng; Siti Nor Aisyah Ishak (Penerbit Universiti Kebangsaan Malaysia, 2018)
Written corrective feedback (WCF) is widely used among writing teachers in attempt to improve students’ language accuracy in their written tasks. Experts of second language (L2) writing stated that WCF plays a significant role in language accuracy development because it is related to the development and improvement of students’ accuracy in second language writing. Corrective feedback can be grouped into direct WCF and indirect WCF. However, results in many past empirical studies were inconclusive because of variation in how the effectiveness of WCF was measured. Additionally, there is a lack of investigation pertaining to the students’ perceptions toward the feedback they received, which may reveal important factors that influence the students’ reception of the feedback that resulted in performance changes. Hence, the purpose of this study is to explore factors that contributed to the accurate use of the past tenses resulting from direct WCF and indirect WCF. Interviews were conducted with 12 students and the qualitative findings revealed the following factors: 1) learner attitudes towards feedback provided, 2) learner beliefs towards what corrections entailed, and 3) types of scaffolding. Additionally, the findings revealed the importance of teacher-student conference, the need for students to be trained over a longer period of time in relation to the use of error codes and the need for instructor to understand and implement direct and indirect feedback accordingly in their teaching.